A multi-level spatio-temporal analysis on prostate cancer outcomes. (June 2021) - Wah, Win; papa, Nathan; Evans, Melanie; Ahern, Susannah; Earnest, Arul
Highlights: Used Bayesian spatial-temporal multilevel models to explain variation in PSM. Aggressive tumour characteristics (NCCN risk) was the main contributor to PSM. Increasing NCCN risk and Public surgical institution influenced high PSM risk. Robotic, laparoscopic RP, high-volume surgeons, affluence influenced low PSM risk. PSM was related to higher 5-year all-cause and prostate cancer-specific mortality. Abstract: Background: Geographic and temporal variation in positive surgical margins (PSM) for prostate cancer after radical prostatectomy (RP) has been observed. However, it is unclear how much of this variation could be attributed to patient, surgeon, institution, or socioeconomic-related factors and the impact of PSM on death among localized prostate cancer patients. Methods: This study aimed to assess the independent and relative contribution of the patient, surgeon, institution and area-level risk factors on geographic and temporal variation of PSM and evaluate the impact of PSM on five-year all-cause and prostate cancer-specific mortality among localized prostate cancer patients. Within the hierarchical-related regression approach, we utilised Bayesian spatial-temporal multi-level models to study individual and area-level predictors with the outcomes, while accounting for geographically structured and unstructured correlation and non-linear trends. Results: Individual-level data included 10, 075 localized prostate cancer cases with RP reported to the Prostate Cancer Outcomes Registry Victoria between 2009 and 2018. Area-level data comprised socio-economic disadvantage and remoteness data at the local government area level in Victoria, Australia. 26 % of patients had PSM, and the rates varied across areas by years. This variation was mainly associated with NCCN risk, followed by RP techniques, surgical institution type, surgeon volume and socio-economic disadvantage. Intermediate (Odds ratio/OR = 1.21, 95 % credible interval/Crl = 1.05−1.41), high/very-high risk groups (OR = 2.24, 95 % Crl = 1.91−2.64) and public surgical institution (OR = 1.64, 95 % Crl = 1.46−1.84) were independently associated with a higher likelihood of PSM. Robot-assisted (OR = 0.61, 95 % Crl = 0.55−0.68), laparoscopic RP (OR = 0.76, 95 % Crl = 0.62−0.93), high-volume surgeon (OR = 0.84, 95 % Crl = 0.76−0.93) and socio-economically least disadvantaged status (OR = 0.78, 95 % Crl = 0.64−0.94) showed a lower likelihood of PSM. PSM was also independently associated with a higher five-year all-cause and prostate cancer-specific mortality. Conclusion: Aggressive tumour characteristics and RP techniques were the main contributors to the likelihood of PSM following RP. Reducing the prevalence of PSM will generally improve prostate cancer-specific and all-cause mortality.